Macrocompetências para o currículo dos programas de residência em medicina de família e comunidade de Fortaleza, Ceará - Bomfim, André Luis Benevides (2014)
The lack of a skills-based curriculum to guide and qualify the residents` education is a reality in several Residency programs in the country. This vulnerability has been discussed by residents, preceptors and coordination of the residency program of family and community medicine (PRMFC), which generated the need of the development of this research. This fact brings the following vulnerabilities: lack of clarity of the learning objectives, educational strategies and the evaluation to be addressed to the residents. Initially, a literature review of the competency-based curricula and a review of documents prepared by associations, societies and professional bodies were conducted. Then we conducted a teacher training course for the preceptors of the PRMFC, with discussions on the theoretical bases of the competency-based curriculum; active learning methodologies; planning and conducting educational activities and strategies; and learning evaluation. After this training, workshops were held for the development of an array of macro competencies. This work trained 12 preceptors of PRMFC and allowed the construction of an array of macro competencies. It will surely facilitate the teaching-learning process in a two-year Residency Program, evaluating the skills of the residents at the end of the course, which guarantees to society a professional able to develop its actions. With a competency-based curriculum specific designed for Family Medicine and for Primary Health Care, we wish to reorient the teaching-learning processes of residents and preceptors to qualify clinical practice.